Wailing alarm system / Mohamad Aizollah Akim Adnan, Hisyamuddin Ahdi and Ahmad Firdaus Kamaruddin - Adnan, Mohamad Aizollah Akim; Ahdi, Hisyamuddin; Kamaruddin, Ahmad Firdaus (2013)
Our product determine by the peacefulness environment. This type of product shows us that the sound that harm to use in long term. This product use in the silent area. The area that supposed to be quiet such as library, hospital and etc. People today just ignore this silent area. Maybe cause of their attitude or their lack of alertness. From this situation, we have interest in making this product. By this way, this product will alert them this is the silent area. If noise level is over 80dB, 8 hours a day, then you are living in a dangerous environment.